Microstructure and mechanical properties of additive manufacturing AlSi10Mg alloy using direct metal deposition. (25th January 2018) - Chen, Bo; Yao, Yongzhen; Song, Xiaoguo; Tan, Caiwang; Cao, Liang; Feng, Jicai
ABSTRACT: Laser direct metal deposition was used to manufacture AlSi10Mg alloy in this study. The microstructure and mechanical properties of the additive manufacturing AlSi10Mg alloy, and the influence of scanning speed on the performance of the manufactured specimen were investigated. Further hardness and tensile tests showed that with the decrease of scanning speed, micro-hardness of the manufactured parts decreased, but the tensile property increased. The mechanical properties of the manufactured components exceeded the mechanical properties of AlSi10Mg alloy casting parts, which indicated that the direct metal deposition process was suitable for manufacturing AlSi10Mg alloys.